Unsteady extension of quasi-steady physical modeling and experimental verification of a magnetorheological energy absorber - Zou, Zhiyuan; Zhang, Honghui; Liao, Changrong; Wang, Ning (Frontiers in Materials, 2022)
Magnetorheological (MR) fluids are promising in controllable damping based on regulated apparent viscosity under magnetic field control, and they are employed in various damping devices such as automotive dampers and energy absorbers for artillery or landing gears by medium substitution with structural adaptations. In this study, we designed and fabricated a magnetorheological energy absorber (MREA) with disc springs as re-coiling parts, modeled the MR fluid flow based on the Bingham constitutive model, and then carried out un-steady extension based on the quasi-steady model. The experimental tests of the MREA show that the unsteady extension of the quasi-steady model can designate the behaviors of the MREA in different impact speeds better than the original; thus, the controllability of the MREA is verified. An interesting phenomenon, where a rippled MREA peak force is observed at the saturated excitation when the impact speed is not so high and disappears when the impact speed is high enough, is accounted from the viewpoint of flow modeling and finally verified by more experimental results.